The role of epithelial–mesenchymal transition (EMT)-associated genes during gonadogenesis of albino rat - Lina A. Aeshra; Maiada Moustafa; Mohammed I.Y. Elmallah; Said Abdelrahman Salih; Ibrahim Y. Abdel Kader (Journal of Basic and Applied Zoology, 2020)
Abstract Background The epithelial mesenchymal transition (EMT) plays a critical role in normal embryonic development as well as abnormal pathological events such as tumor formation and metastasis. One of these important events that may explain this phenomenon during embryogenesis is the migration of primordial germ cells (PGCs) from hindgut into the genital ridge during gonadogenesis. Yet, more studies are needed to explain the molecular changes underlying the role of EMT during gonadogenesis. Here, we aimed to study the molecular changes of four genes to determine whether the EMT occurs during gonadogenesis. These studied genes are alkaline phosphatase (ALP) as PGC marker, E-cadherin (CDH1) as epithelial marker, vimentin (VIM) as mesenchymal marker, and signal transducer and activator of transcription 3 (STAT3) as migration regulator and differentiation marker. Results The results showed a substantial decrease in the expression of ALP by the increase of the embryonic age. The expression of CDH1 is inversely proportional to the expression of VIM during the days of PGC migration. STAT3 expression related to the time of occurrence of migration and differentiation. Conclusion Taken together, our findings demonstrated the molecular changes of ALP, PGC, CDH1, and VIM during the process of gonadogenesis. Further studies are warranted to understand other molecular mechanisms associated with gonadogenesis.